Albert Einstein Memorial Lectures. - Mechoulam, Raphael (World Scientific, 2012)
This volume consists of a selection of the Albert Einstein Memorial Lectures presented annually at the Israel Academy of Sciences and Humanities. Delivered by eminent scientists and scholars, including Nobel laureates, they cover a broad spectrum of subjects in physics, chemistry, life science, mathematics, historiography and social issues. This distinguished memorial lecture series was inaugurated by the Israel Academy of Sciences and Humanities following an international symposium held in Jerusalem in March 1979 to commemorate the centenary of Albert Einstein's birth. Considering that Einste.